Effectiveness Of New Pedagogical Technologies In Organizing Professional Legality Of Students In Teaching Physics - Eshtuhtarova Orzigul Shonazarovna (Genius Journals, 2023)
Today, with the rapid introduction of information and communication technologies in the educational process, it remains one of the most favorable factors in increasing the effectiveness of education. Bringing the education system up to world standards is one of the important tasks of the modern education reforms. In the process of advanced training, a computer science teacher gives special courses on informatization and education management, and also masters innovative pedagogical and information and communication technologies, new software tools, creative activity in their use, creativity, studies the development of topics in the field of science on the use of innovative pedagogical technologies and interactive methods, as well as the wide promotion of their innovative activities.
Keywords: formation of culture; training and education; environmental education